PERAN KONTEN POST INSTAGRAM DALAM KEBERLANJUTAN BISNIS - Rachmasari, Devi; Askandari, Sabrina (Politeknik Ubaya, 2024)
The pandemic hit the education sector, including courses. Many courses shifted to online marketing and online classes. A course that the writer conducted the study, from rarely engaged in online marketing, conducted Instagram Marketing to solved the problem due to the huge potential for growing the brand of the course. Instagram users engage with the content often, using its interactive capabilities to reach the largest possible audience was as potential customers for the course. The writer utilized qualitative method for the study. Indeed it helped the course gained customers and maintained business sustainability. Budding entrepreneurs leveraging profitable online business ideas often begin their product promotion on social platforms. Brands are a little hesitant at the beginning but sooner they also adopt different product promotion strategies to expand brand reach.Therefore, businesses of all kinds — whether a startup or an established brand — should elevate their Instagram marketing strategy for a powerful brand presence to attract and engage with potential customers. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License